Multilingual social media platform for tourist centres in Uganda - Fagbolu, Olutola Olaide; Chukwunonso Stanley, Edu; Adekunle Joseph, Adewale (Open Science Journal, 2022)
Tourism is an important source of revenue in Africa which has not been properly harness to generate expected income in Uganda hence the need to develop a social media app called TourIt. TourIt will showcase landscapes, rich history of ancient and cultural heritages, water bodies (lakes and rivers), wild safari expeditions, artefacts and facilitate user-centred design, interactive information-sharing, interoperability and collaboration on tourism with multi languages such as Luganda, English, Swahili, Yoruba, Ibo for now while other languages can be added as the app evolves. The app was developed using Android Studio XML for graphical user interface, Firebase for database, Java and XML for coding while Javascript handles several modules including functions in the database and automatic restoration of multiple languages were done with MBL (Memory Based Learning), CRF (Conditional Random Field) and rule expressions which were implemented in UML class of Python Programming Language with NLTK (Natural Language Tool Kit). This social media app will create and co-create tourism-based content, edit the content, rate whenever it is necessary. Comment will be done by the app on content whenever it is necessary, content can be discussed, content can be tagged and organized, content can be shared or personalized and content can be mashed with other contents so as to promote rich cultural values, natural endowment and attractive places in Uganda.